PENAMBAHAN KAFEIN PADA PAKAN KOMERSIAL TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN UDANG GALAH (Macrobrachium rosenbergii) - Putri, Vira Riana; Diansyah, Sufal; Mahendra, Mahendra; Syahputra, Hafif; Zulfadhli, Zulfadhli; Ibrahim, Yusran (Universitas Teuku Umar, 2021)
This study aimed to determine the effect of caffein with various doses on the survival rate and gorwth of galah shrimp (Macrobrachium rosenbergii). This research using completely randomized design with five treatments and three replications. Caffeine is given through the feed at a doses 0,0; 0,5; 1,0; 1,5; and 2,0 g caffein/kg feed. The result showed that applied caffein in commercial feed has a significant effect (P < 0,05) on the survival rate of galah shrimp. And no significant effect (P > 0,05) on absolute weight growth and relative growth rate of galah shrimp. Survival rates range from 35% - 80%, absolute weigh growth range from 0,4 – 0,46 g and relative growth rate range from 1,05 – 1,31% / days. The best treatment is P5 (2 g caffein/kg feed) with an 80% survival rate; and 0,46 g absolute weight growth; and 1,31% / days relative growth rate. pH range from 6,4-7,4; temperature range from 25-30 oC. The results of these water quality parameters indicate normal water quality for galah shrimp survival.